Application of biochar in advanced oxidation processes: supportive, adsorptive, and catalytic role - Faheem; Du, Jiangkun; Kim, Sang Hoon; Hassan, Muhammad Azher; Irshad, Sana; Bao, Jianguo (SPRINGER HEIDELBERG, 2020)
The advanced oxidation processes (AOPs), especially sulphate radical (SO4 center dot-)-based AOPs (SR-AOPs), have been considered more effective, selective, and prominent technologies for the removal of highly toxic emerging contaminants (ECs) due to wide operational pH range and relatively higher oxidation potential (2.5-3.1 V). Recently, biochar (BC)-based composite materials have been introduced in AOPs due to the dual benefits of adsorption and catalytic degradation, but the scientific review of BC-based catalysts for the generation of reactive oxygen species (ROSs) through radical- and non-radical-oriented routes for EC removal was rarely reported. The chemical treatments, such as acid/base treatment, chemical oxidation, surfactant incorporation, and coating and impregnation of minerals, were applied to make BC suitable as supporting materials (SMs) for the loading of Fenton catalysts to boost up peroxymonosulphate/persulphate/H(2)O(2)activation to get ROSs including(center dot)OH, SO4 center dot-,O-1(2), and O(2)(center dot-)for targeted pollutant degradation. In this review, all the possible merits of BC-based catalysts including supportive, adsorptive, and catalytic role are summarised along with the possible route for the development prospects of BC properties. The limitations of SR-AOPs especially on production of non-desired oxyanions, as well as disinfection intermediates and their potential solutions, have been identified. Lastly, the knowledge gap and future-oriented research needs are highlighted.
Keywords: ACTIVATED PERSULFATE OXIDATION; WASTE-WATER TREATMENT; COBALT-MEDIATED ACTIVATION; ZEROVALENT IRON COMPOSITE; OXYGEN SPECIES GENERATION; DISINFECTION BY-PRODUCTS; PERSISTENT FREE-RADICALS; FENTON-LIKE REACTION; ZERO VALENT IRON; HYDROGEN-PEROXIDE